PENGEMBANGAN CD PEMBELAJARAN INTERAKTIF KIMIA SMA BERBASIS INTERTEKSTUALITAS ILMU KIMIA SEBAGAI ALTERNATIF MODEL PEMBELAJARAN - Anwar, Sjaeful (Jurnal Pengajaran MIPA, 2010)
Chemistry learning based on the intertextuality of chemistry demands relationship among chemistry representsation on three levels, which are macrocospic, microscopic, and symbol level with the daily experience of students and the social interaction developed by teachers. Through the research entitled â€œPengembangan CD Pembelajaran Interaktif Kimia SMA Berbasis Intertekstualitas sebagai Alternatif Model Pembelajaranâ€, we will have a learning CD for teachers using competency standard and basic competency; concepts and indicators; the representation of chemistry materials on three levels macroscopic, microscopic, and symbol; learning description; and student work sheet. Before making the learning model, we will execute a standard analysis on the content of KTSP 2006, so we will get the concepts and indicators; potray the learning process of teachers in class and analyse the reference books both text books and hig school books. The data source for this research is the table of according to concept and indicators with competency standard and basic competency; the observation of learning process in class; the analysis table of three levels; hydrolysis materials from text books in high school and university; and the descriptive table of hydrolysis concept learning. The supporting instruments used are quistionaires to know the students expereince and essay texts to know the concept understanding the students have after the learning process. From the standard analysis of the content of KTSP 2006, we have three concepts and eight indicators. The first concept is classifying salt according to the forming compounds with the indicators (1) explain salt coming from strong acid and strong base; (2) explain salt coming from strong acid and weak base; (3) explain salt coming from weak acid and strong base; (4) explaining salt coming from weak acid and weak base. The second concept: hydrolysis is the ions reaction with water molecul producing ion H+ and or OHwith indicators (1) describe salt hydrolysis and (2) explain various kinds of salt hydrolysis. The third concept is salt undergoing hydrolysis can be acid base, or neutral with indicators (1) measure qualitatively the characteristic of acid, base, and neutral of salt by using some indicators and (2) count the ph of hydrolysied salt condensation. The observation result will be recorded on video then transcribed into text and smoothed to be a basic text. After that, we will do propotition degradation to gain global structure. Then, this data will be classified based on the intertextuality of chemistry. From the result of the data analysis we can conclude that the model teacher has not used the learning based on the intertextuality chemistry yet. The learning process of the model teacher is dominated by the symbol level and the social interaction developed by the teacher is not optimal; besides, there is no aspect of daily experience discussed in the learning process. The development of learning model based on intertextuality begins by making hydrolysis material representation in three levels. The compilation of hydrolysis material representation is executed in three steps: analysing high school books and university; making representation device; conducting validation to experts and practitioners; and final revision. In macroscopic level we do demonstration of the condensation and litmus test on soaps, alum, and salt and also the determination pH of the salt by using pH meter. In microscopic level we demonstrate pictures of species salt solution before and after hydrolysis process. Then in symbolic level we demonstrate the formula of salt molecul, ionisation reaction equation and hydrolysis on salt, and mathematic formula in determining the concentration H+ and OHto count pH and pOH. Later on, we make a description of the learning process equiped with learning media; clarify the demonstrations; present the model in front of experts and practitioners; record it in a learning CD. Meanwhile, the application of the learning CD in class will be conducted in the next research in the second year.